Study of the phase composition, structure and mechanical properties of synthetic composites produced by high-temperature vacuum sintering of SHS-fabricated CrNi-TiN powders - Matveev, Alexey E.; Promakhov, Vladimir V.; Schulz, Nikita; Bakhmat, Vladislav; Babaev, Artem; Vorozhtsov, Alexander B. (Metals)
This work studies the phase composition, structure and mechanical properties of composite materials obtained by high-temperature vacuum sintering of SHS-fabricated CrNi–TiN powders synthesized in semi-industrial-scale production conditions. It was found that changes in the synthesis conditions have no effect on the phase composition and structure of the final products. Additionally, a small increase in the average size of ceramic TiN particles was observed. Compacted rectangular samples were obtained by high-temperature vacuum sintering of fine-ground CrNi–TiN SHS products. A minimum sintering temperature was found at which specimens with a density of 95% of the theoretical one could be obtained. The structure of sintered composites inherits the metal-matrix structure of a part of SHS products. It was shown that CrNi–TiN composite materials are superior to NiTi–TiB2 composites in terms of hardness as well as binding strength for three-point bending at temperatures up to 550